Burkina Faso Social Safety Nets - Cherrier, Cecile; del Ninno, Carlo; Razmara, Setareh (World Bank, Washington, DC, 2014)
This report provides an inventory of safety net programs in Burkina Faso and suggests policy measures that could increase their coverage, efficiency, and sustainability. It shows that the scope and coverage of the existing safety nets is too limited. Most interventions are small and temporary. On average, excluding subsidies, annual spending on safety nets constituted only 0.6 percent of GDP while about 20 percent of the population is food-insecure and chronically poor. Food transfers are the main safety net program, accounting for 69 percent of total spending and over 80 percent of all beneficiaries. Most of the financing for safety nets is external. The report recommends developing a safety net system that adequately responds to the needs of the poor.